Getting to the root of scales, feather and hair: As deep as odontodes?. Issue 4 (25th August 2017) - Dhouailly, Danielle; Godefroit, Pascal; Martin, Thomas; Nonchev, Stefan; Caraguel, Flavien; Oftedal, Olav
Abstract: While every jawed vertebrate, or its recent ancestor, possesses teeth, skin appendages are characteristic of the living clades: skin denticles (odontodes) in chondrichthyans, dermal scales in teleosts, ducted multicellular glands in amphibians, epidermal scales in squamates, feathers in birds and hair‐gland complexes in mammals, all of them showing a dense periodic patterning. While the odontode origin of teleost scales is generally accepted, the origin of both feather and hair is still debated. They appear long before mammals and birds, at least in the Jurassic in mammaliaforms and in ornithodires (pterosaurs and dinosaurs), and are contemporary to scales of early squamates. Epidermal scales might have appeared several times in evolution, and basal amniotes could not have developed a scaled dry integument, as the function of hair follicle requires its association with glands. In areas such as amnion, cornea or plantar pads, the formation of feather and hair is prevented early in embryogenesis, but can be easily reverted by playing with the Wnt/BMP/Shh pathways, which both imply the plasticity and the default competence of ectoderm. Conserved ectodermal/mesenchymal signalling pathways lead to placode formation, while later the crosstalk differs, as well as the final performing tissue(s): both epidermis and dermis for teeth and odontodes, mostly dermis for teleosts scales and only epidermis for squamate scale, feather and hair. We therefore suggest that tooth, dermal scale, epidermal scale, feather and hair evolved in parallel from a shared placode/dermal cell unit, which was present in a common ancestor, an early vertebrate gnathostome with odontodes, ca. 420 million years ago.